Lymphatic drainage of the brain - Carare, Roxana O. (Henry Stewart Talks, 2023)
Lymphatic drainage of the brain, Protein clearance from the CNS, Drainage pathways for cerebrospinal fluid (CSF) and interstitial fluid (ISF), Alzheimer’s disease, Intramural periarterial drainage (IPAD) pathway, Amyloid-related imaging abnormalities with edema or effusion, Cerebral amyloid angiopathy (CAA), Enlarged perivascular spaces, Therapeutic targets for IPAD